Buzz Marketing: Effective Strategy for Increasing Sales in the Digital Era - Dewi Indriani Jusuf (Jurnal Sosial Sains dan Komunikasi, 2023)
The digital era has changed the marketing landscape dramatically, forcing companies to adapt to changing consumer trends and preferences. Buzz Marketing has been recognized as one of the powerful approaches to harness the power of social networks and virality of content on digital platforms. This research aims to investigate the effectiveness of the Buzz Marketing strategy in increasing sales in the digital era. Qualitative approach with descriptive methods. The research results show that implementing a buzz marketing strategy, through viral content, influencer campaigns, user interaction, interactive promotions, and user-generated marketing, can significantly improve a company's sales performance in the digital era. By harnessing the potential of buzz marketing, companies can expand their brand reach, build deeper engagement with consumers, and strengthen their brand image online. In conclusion, the use of innovative and adaptive marketing strategies, supported by the strong influence of buzz marketing, has proven to be the key to achieving marketing success amidst increasingly fierce competition in the ever-growing digital market.